Spatial Persistence of High Strain Events During Brittle Failure - Jessica McBeck; Benoît Cordonnier; Wenlu Zhu; François Renard (Geophysical Research Letters, 2024)
Abstract The onset of brittle failure in rocks includes dilatancy and strain localization. To better understand this nucleation process, we analyze the evolution of the local three‐dimensional strain tensor using X‐ray tomograms acquired during triaxial compression experiments on granite and sandstone. The onset of the localization of the compaction, dilation, and shear strain occurs when ∼65% of the rock volume experiences dilation. Tracking the locations of the high strains throughout loading suggests that the deformation that occurs early in loading influences the location of the system‐sized fracture network that produces macroscopic failure. This influence is larger in the sandstone experiments than the granite experiments, likely due to the microstructure of the sandstone. These results have important implications for detecting precursors to catastrophic failure.